Innovative Technical Solution Using the Renal Artery Stump after Nephrectomy as an Inflow Artery for Lower Limb Revascularization—A Case Report - Russu, Eliza; Mureșan, Adrian Vasile; Kaller, Reka; Toma, Lucian; Coșarcă, Cătălin Mircea; Chibelean, Călin Bogdan; Arbănași, Emil Marian; Arbănași, Eliza Mihaela (Frontiers in Surgery, 2022)
We present the case of a 56-year-old patient admitted to the vascular unit of the Targu Mures County Emergency Clinical Hospital after a computed tomography angiography performed for critical limb ischemia showed a tumor of the right kidney of 11.3/12/11 cm anteroposterior/later-lateral/craniocaudal, accompanied by an abdominal aortic aneurysm (AAA) (3 cm diameter) and right iliac artery occlusion. An interdisciplinary team formed of urological and vascular surgeons decided and performed a one-step operation. The right kidney was removed, and the limb revascularization was achieved by performing a bypass that used the right renal arterial stump as an inflow artery, thus called a reno-femoral bypass. The AAA had no indication for reconstruction. The final pathology interpretation of the kidney tumor revealed a clear cell renal cell carcinoma, excised with oncological safety margins. A short-term follow-up found the patient without ischemic symptomatology and a fully functional graft.